2016
DOI: 10.1111/ceo.12720
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Macular Edema at the time of Cataract Surgery trial: a prospective, randomized clinical trial of intravitreous bevacizumab versus triamcinolone in patients with diabetic macular oedema at the time of cataract surgery – preliminary 6 month results

Abstract: Background: To compare visual and anatomical outcomes between intravitreous bevacizumab (BVB, Avastin) and triamcinolone (TA, Triesence) when administered at the time of cataract surgery in patients with diabetic macular oedema (DME).Design: Prospective, single-masked, randomized clinical trial at The Royal Victorian Eye and Ear Hospital, Melbourne.Participants: Patients with clinically significant cataract and either centre-involving DME or DME treated within the previous 24 months.Methods: Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
(96 reference statements)
1
43
0
2
Order By: Relevance
“…Recently, intravitreal injections of VEGF agents such as bevacizumab, ranibizumab, and aflibercept have become the standard therapy for DME worldwide [6,7]. However, these agents do not significantly reduce the macular thickness in eyes with DME after CS [8,9]. This is probably because cytokines other than VEGF are involved in the onset and the progression of DME after CS [5], and anti-VEGF agents cannot reduce the levels of these other cytokines in eyes with DME [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, intravitreal injections of VEGF agents such as bevacizumab, ranibizumab, and aflibercept have become the standard therapy for DME worldwide [6,7]. However, these agents do not significantly reduce the macular thickness in eyes with DME after CS [8,9]. This is probably because cytokines other than VEGF are involved in the onset and the progression of DME after CS [5], and anti-VEGF agents cannot reduce the levels of these other cytokines in eyes with DME [10].…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized prospective clinical trial demonstrated that IVTA can reduce central macular thickness (CMT) for 6 months after CS in eyes with DME, but that intravitreal bevacizumab injection did not reduce CMT even after multiple injections [9]. Thus, IVTA may be better than anti-VEGF injections after CS for the treatment of DME.…”
Section: Introductionmentioning
confidence: 99%
“…Although visual acuity may decrease after cessation of treatment, visual acuity recovered in most patients after retreatment with NSAID eye drops. 49,50 Moreover, small studies suggest that a combination treatment with a topical corticosteroid and NSAID is more effective than a topical corticosteroid alone. The time to resolution of PCME was significantly shorter in patients treated with a combination of topical corticosteroids and NSAIDs.…”
Section: Treatmentmentioning
confidence: 99%
“…Increased IOP is a common complication of local corticosteroid administration, but prevalence may vary between various routes of administration. [48][49][50][51] Other routes of corticosteroid administration may also prevent the occurrence of CME, involving a lower incidence of IOP increase. Previous studies have investigated the use of high frequency prednisolone eye drops, oral prednisolone, intravitreal TA, and subtenon TA.…”
Section: Prevention Of Cystoid Macular Edema In Diabeticsmentioning
confidence: 99%
See 1 more Smart Citation